Caracterización Fisicoquímica y organoléptica de vino de Mango (Mangifera Indica L.) Obtenido a partir de tres tipos de tratamiento con azúcares (Journal on studies and research of academic knowledge, 2016)
The objective of this research was to characterize physicochemical and organoleptically the mango wine (Mangifera Indica L), coming from three types of treatments with different types of sugars applied to the must prior to the fermentation process; to provide useful information in the elaboration Of mango wine for the use of mango fruits in the department of Itapúa, and in mango producing regions in Paraguay. The design was completely randomized with 3 treatments M1, M2, M3 and 3 repetitions of each, with added refined white sugar and brown sugar, and without added sugar, previously adjusting the Total Acidity and Ionic Acidity of the must. The treatments were carried out in bioreactors of 5 liters capacity. Inoculated with 1 g/L of Saccharomyces cerevisiae and stationed at 25°C for 15 days; then decanted, bottled, corked and parked for 75 days. The M2 treatment with brown sugar presented the highest value of alcoholic strength, while the treatment with white sugar M1 the highest value of Soluble Solids (p
Keywords: wine; mango; sugar